Plasmodium falciparum is dependent on de novo myo‐inositol biosynthesis for assembly of GPI glycolipids and infectivity. Issue 4 (16th January 2014) - MacRae, James I.; Lopaticki, Sash; Maier, Alexander G.; Rupasinghe, Thusitha; Nahid, Amsha; Cowman, Alan F.; McConville, Malcolm J.
Summary Intra‐erythrocytic stages of the malaria parasite, Plasmodium falciparum, are thought to be dependent on de novo synthesis of phosphatidylinositol, as red blood cells (RBC) lack the capacity to synthesize this phospholipid. The myo‐inositol headgroup of PI can either be synthesized de novo or scavenged from the RBC. An untargeted metabolite profiling of P. falciparum infected RBC showed that trophozoite and schizont stages accumulate high levels of myo‐inositol‐3‐phosphate, indicating increased de novo biosynthesis of myo‐inositol from glucose 6‐phosphate. Metabolic labelling studies with 13C‐U‐glucose in the presence and absence of exogenous inositol confirmed that de novo myo‐inositol synthesis occurs in parallel with myo‐inositol salvage pathways. Unexpectedly, while both endogenous and scavenged myo‐inositol was used to synthesize bulk PI, only de novo‐synthesized myo‐inositol was incorporated into GPI glycolipids. Moreover, gene disruption studies suggested that the INO1 gene, encoding myo‐inositol 3‐phosphate synthase, is essential in asexual parasite stages. Together these findings suggest that P. falciparum asexual stages are critically dependent on de novo myo‐inositol biosynthesis for assembly of a sub‐pool of PI species and GPI biosynthesis. These findings highlight unexpected complexity in phospholipid biosynthesis in P. falciparum and a lack of redundancy in some nutrient salvage versus endogenous biosynthesis pathways.